PENERAPAN TEKNIK MNEMONIK PADA KETERAMPILAN MENULIS BAHASA JERMAN KELAS XI - Abigail, Bethany Claudine; Indriwardhani, Sri Prameswari (J-EDu: Journal - Erfolgreicher Deutschunterricht, 2025)
This study aims to describe the results of the application and student responses from the application of mnemonic techniques in German writing skills of class XI-K SMA Negeri 1 Tumpang. This study used descriptive qualitative method and involved 33 students as research subjects. The results of the observation data showed that the application of mnemonic techniques was carried out smoothly and well, students who participated in the lesson were also active and enthusiastic. The results of student responses show a positive reaction to the mnemonic technique which can be easily understood and helps students in German learning activities. In addition, students also feel more interested and agree if this technique is used as an option in learning German.